Etnolingvistiniai santykiai priešistorinėje Šiaurės rytų Europoje - Bednarczuk, Leszek (Baltistica, 1977)
ETHNOLINGUISTIC  SITUATION IN THE PREHISTORIC NORTH-EAST  EUROPEThe hitherto known facts allow to state that in the period between the disintegration of Indo-European community and the expansion of Mongolian-Turkic peoples four groups of languages: Germanic, Balto-Slavic, Finno-Ugrian and Iranian, connected with one another, existed in the North-East Europe. With the exception of Germanic-Iranian, the existence of contacts between all the remaining groups is assumed, where only the Baltic-Iranian contacts have not been proved to this day. As to Baltic-Slavic connections, apart from similarities resulting from common heritage, they are very late and they go beyond the epoch which comes into question. No certain Baltic borrowings in common Slavic and vice versa no Slavic borrowings in common Baltic have as yet been stated. There are only Polish loan-words in Old Prussian as well as East Slavic and Polish terms in Lithuanian and Latvian. Moreover, some local Baltic influences in the neighbouring Slavic languages have been found. The prehistoric Baltic-Germanic contacts were rather scarce and late and, as it seems, mainly Scandinavian languages were the direct source of Germanic borrowings in Baltic (in the case of Old Prussian it was also Gothic). The Baltic-Finno-Ugrian contacts embraced West Finnic and Volga Finnic languages only, but they were close and prolonged. The Baltic loan-words in West Finnic are numerous (about two hundred), whereas to the unquestionable borrowings in Volga Finnic belong only five words in Mordvian. The Finno-Ugrian borrowings in Baltic are less frequent (about forty words). Most of them come from West Finnic and here also a few words of Iranian and Germanic origin occur. Some of them are known in Slavic languages which allow us to state that they may have dated back to Balto-Slavic epoch.